A stem rust resistance gene from rye in Selection 212 - D. SINGH, J.B. SHARMA and (Indian Phytopathology, 2003)
Selection 212, a stem rust resistant line, was developed by homologous recombination between wheat and rye (Secale cereaie) chromosomes using monosomic for chromosome 5B of variety Chinese Spring, a self compatible rye strain and Sonalika as backcross parent. Sel.212 was resistant at seedling stage to 20 pathotypes of Puccinia graminis f. sp. tritici. Of these, pathotype 21 (9G5) was selected for genetical and cytogenetical analysis of Sel.212 because of its avirulence on parental lines rye and Sonalika so that the resistance contributed by both rye and Sonalika in Sel.212 can be identified. The present communication reports the nature and number of genes controlling resistance against this pathotype and their location on specific chromosome of Sel.212.